Effects of Educational Music Therapy on State Hope for Recovery in Acute Care Mental Health Inpatients: A Cluster-Randomized Effectiveness Study - Silverman, Michael J. (Frontiers in Psychology, 2016)
Background: There has been an increasing emphasis on recovery as the expectation for people with mental health disorders. Purpose: The purpose of this effectiveness study is to determine if group-based educational music therapy can immediately impact state hope for recovery in acute care mental health patients. Research questions included: Will acute care mental health inpatients who participate in a single music therapy session have higher agency and pathway aspects of state hope for recovery than patients in a control condition? Will there be differences in state hope for recovery as a result of hope-oriented songwriting or lyric analysis interventions? Method: Participants (N = 169) were cluster randomized to one of three single-session conditions: lyric analysis, songwriting, or wait-list control. Results: There was no significant between-group difference. However, both music therapy conditions tended to have slightly higher mean pathway, agency, and total state hope scores than the control condition even within the temporal parameters of a single music therapy session. There was no between-group difference in the songwriting and lyric analysis interventions. Conclusions: Although not significant, results support that educational music therapy may impact state hope for recovery within the temporal parameters of a single session. The specific type of educational music therapy intervention did not affect results. Implications for practice, limitations, and suggestions for future research are provided.